Problems of research of information and communicative processes in political sphere (Herald of Journalism, 2021)
The role of information in the life of a human and the state, individual social groups and society is very important. Information is also a tool for communication between the authorities and the target group. In other words, the communication of the state with various categories of society in domestic and foreign policy is carried out through information.The purpose of the study - to focus on the main issues in the study of information and communica- tion processes in the political system of the state; analysis of the theoretical and methodological bases of the study of the concepts of “information” and “communication”; identification of state features in the study of information and communication processes in the political sphere. The authors also aim to reveal the main stages in the emergence and development of political communication between political players.The object of research is information and the relationships formed through it, is communication.Applied social research methods were used in the work. Quantitative and qualitative research, in particular, questionnaires, expert analysis of the works of domestic, western and russian researchers, classifications were made on the methodological basis of the study.The results of the study are of great practical importance in the implementation of information and communication processes in the state political system. The results of the work can be used in the meth- ods of political science and journalism, political communication in the media.Key words: information, communication, politics, society, management.